PENGARUH PELAKSANAAN PROMOSI TERHADAP MINAT KONSUMEN PRODUK OTOMOTIF (KASUS DEALER PT. AGUNG AUTOMALL CABANG UJUNG BATU KABUPATEN ROKAN HULU) - Sari, Anggraini Novita; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study was conducted to investigate the implementation of the promotion in PT. Agung Automall, to determine consumer interest in PT. Agung Automall and to determine the effect the implementation of the campaign against the consumer interest in PT. Agung Automall. The formulation of the problem as follows: How does the implementation of the promotion of the interest of consumer automotive products PT. Agung Automall Branch tip Kab.Rokan stone Hulu.This research is a descriptive study using a qualitative approach as a tool of analysis. This research was conducted at PT. Agung Automall Branch tip Kab.Rokan stone Hulu is located at Jl. Sudirman Kec.ujung Kab stone. Rokan Hulu. Determination of making the number of respondents (samples) conducted through accidental sampling technique using Slovin formula specified number of samples in this study as many as 52 customers. Data collection techniques of observation, interviews and documentation.Results of this study concluded that the respondents From the results of the promotion of the Dealer PT. Agung Automall Branch. Ujungbatu Kab.Rokan satisfactory whereas Hulu in the category of feedback on the results of consumer interest in Dealer PT. Agung Automall Branch. Ujungbatu Kab.Rokan Hulu in the category of very satisfactory. Through t-test there are variables affect the variable X promotion of consumer interest Dealer PT. Agung Automall Branch. Ujungbatu Kab. Rokan Hulu.Keywords: Promotion, Consumer Interests